Oocyte competence in in vitro fertilization and intracytoplasmic sperm injection patients suffering from endometriosis and its possible association with subsequent treatment outcome: a matched case–control study. (22nd July 2016) - Shebl, Omar; Sifferlinger, Ida; Habelsberger, Alwin; Oppelt, Peter; Mayer, Richard B.; Petek, Erwin; Ebner, Thomas
Abstract: Introduction: Endometriosis affects up to 15% of women of reproductive age. There is an obvious lack of studies dealing with morphological parameters of oocyte morphology in endometriosis patients in assisted reproduction. One aim of the study is to describe oocyte morphology in patients undergoing intracytoplasmic sperm injection suffering from endometriosis. In addition, the impact of endometriosis on in vitro fertilization results is analyzed. Both in vitro fertilization and intracytoplasmic sperm injection patients are then matched with an endometriosis‐free control group for highlighting the possible association of endometriosis with pregnancy outcome. Material and methods: Oocyte morphology of endometriosis patients was assessed in two groups. Both study group and control group consisted of 129 in vitro fertilization/intracytoplasmic sperm injection cycles each. Patients were matched according to anti‐Müllerian hormone, female age, previous treatment cycles, and method of fertilization. Endometriosis was graded according to the revised American Society for Reproductive Medicine guidelines of 1997. Results: Patients with endometriosis had a significantly lower rate of mature oocytes ( p < 0.03) and morphologically normal oocytes ( p < 0.001). In particular, brownish oocytes ( p < 0.009; stage I–IV) and the presence of refractile bodies ( p < 0.001; stage IV) were found to be increased. Endometriosis stage IV was associated with significantly worse‐quality oocytes than stages I–III ( p < 0.01). Fertilization was significantly reduced in conventional in vitro fertilization but not in intracytoplasmic sperm injection ( p < 0.03). This was due to lower fertilization rates in stage III–IV endometriosis compared with stage I–II ( p < 0.04). No difference was observed with respect to rates of implantation, clinical pregnancy, miscarriage, live birth, and malformation. Conclusions: Endometriosis patients, in particular those with severe endometriosis, present lower‐quality oocytes. Once fertilized, no impairment of further preimplantation embryo development and pregnancy outcome right up to healthy live birth rate has to be expected.